2000
DOI: 10.1029/2000jd900118
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of the second and third OH overtones of H2O2, HNO3, and HO2NO2

Abstract: x 10-, (2.8 + 1.0) x 10-, and (3.0 + 1.8) x 10-cm molecules-cm-for H202, HNO3, and HO2NO2, respectively. The uncertainty is for one standard deviation. Assuming excitation of these modes by solar absorption is dissociative for HO2NO2, these measurements confirm that this process will play a small role in the atmospheric photochemistry of the lower stratosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 15 publications
5
63
3
Order By: Relevance
“…Thus, the NIDL provides for a good alternative to both of these methods. Figure 12 shows the NIDL plots drawn using experimental data points for four lower-overtone transitions in the OH stretches of nitric acid and methanol (Brown et al, 2000;Donaldson et al, 1998;Feierabend et al, 2004Feierabend et al, , 2006Lange et al, 2001;Phillips et al, 1998;Zhang et al, 2000) collected by Lane and Kjaergaard (2010), Table XII. Obviously, the NIDL is obeyed rather accurately and hence can be used to make predictions for the higher transitions.…”
Section: Application Of the Nidl For Prediction Of The Higher Overmentioning
confidence: 99%
“…Thus, the NIDL provides for a good alternative to both of these methods. Figure 12 shows the NIDL plots drawn using experimental data points for four lower-overtone transitions in the OH stretches of nitric acid and methanol (Brown et al, 2000;Donaldson et al, 1998;Feierabend et al, 2004Feierabend et al, , 2006Lange et al, 2001;Phillips et al, 1998;Zhang et al, 2000) collected by Lane and Kjaergaard (2010), Table XII. Obviously, the NIDL is obeyed rather accurately and hence can be used to make predictions for the higher transitions.…”
Section: Application Of the Nidl For Prediction Of The Higher Overmentioning
confidence: 99%
“…Since HNO 3 is well reproduced in the upper troposphere an additional conversion of HNO 3 to NO x , as suggested by Jacob et al [1996] for this region to explain the discrepancy found in the NO x /HNO 3 ratio, would therefore be at odds with the simulation of HNO 3 . An additional channel for HNO 4 photolysis at long wavelengths (>760 nm) has been reported [e.g., Zhang et al, 2000;Roehl et al, 2002]. In the model $60 pmol/mol of HNO 4 are calculated at 10 km, insufficient to fully explain the underestimate in NO of $150 pmol/mol.…”
Section: Airborne Measurementsmentioning
confidence: 99%
“…Current recommendations [ DeMore et al , 1997; Sander et al , 2000] indicate very large uncertainties in these parameters (factors of 2 and 5 in the unimolecular decomposition rate coefficients). In addition, spectroscopic studies to carefully quantify photolytic processes in the ultraviolet, visible and near‐infrared spectral regions are also needed to verify those that have been performed [ Zhang et al , 2000]; more recent studies do indicate that near infrared photolysis of HO 2 NO 2 is indeed important [ Roehl et al , 2002]. These uncertainties lead directly to uncertainties in calculated concentrations of these species.…”
Section: Budgets Of Peroxy Radicalsmentioning
confidence: 99%